(3GdRHOI eNJUQ GdejRGf aj GdefWbs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj JbOS ef Cf jhUa HGdMOhK hHYO abO SCdfj eMeO GdeYQha HGdRjf aJM NGf Hf WGZLj Hf LGe Cf CcJH eG jLQj eLQi GdTQM ddTjeI aj GdejRGf bGd GdeUfa QMeg Gddg MGeOG JYGdi s
(3BNQgG (B:s
(3Edi ehVhYGJgG EjLGHjI cGfJ Cj jHQge YdjgG aj Pdc GdYde Cf cGfJ fSHjI hGddg CYde HGdUhGHs
(3Chdg fbhd SfI (B1138 (3g` (B- (3NWhW eNJdaIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
Keywords: (3GdadSaI hGdefWbs